2009
DOI: 10.1111/j.1538-7836.2008.03220.x
|View full text |Cite
|
Sign up to set email alerts
|

New insights into the molecular mechanisms of the fibrinolytic system

Abstract: To cite this article: Rijken DC, Lijnen HR. New insights into the molecular mechanisms of the fibrinolytic system. J Thromb Haemost 2009; 7: 4-13.See also Lijnen R. Retirement of Dé siré Collen. This issue, pp 2-3; Van de Werf FJ, Topol EJ, Sobel BE. The impact of fibrinolytic therapy for ST-segment-elevation acute myocardial infarction. This issue, pp 14-20; Loges S, Roncal C, Carmeliet P. Development of targeted angiogenic medicine. This issue, pp 21-33.Summary. Fibrinolysis is regulated by specific molecula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
257
0
4

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 312 publications
(263 citation statements)
references
References 112 publications
2
257
0
4
Order By: Relevance
“…These interactions are optimised by binding of the key proteins to relevant surfaces, either the surface of a fibrin clot or the surface of endothelial cells lining the blood vessel [26]. Recent research has identified the annexin A2 heterotetramer (AIIt), comprising two molecules of annexin A2 and two of the protein S100A10, as the key endothelial receptor bringing together both plasminogen and tPA to optimise plasmin generation at the surface of the vascular wall [27].…”
Section: Discussionmentioning
confidence: 99%
“…These interactions are optimised by binding of the key proteins to relevant surfaces, either the surface of a fibrin clot or the surface of endothelial cells lining the blood vessel [26]. Recent research has identified the annexin A2 heterotetramer (AIIt), comprising two molecules of annexin A2 and two of the protein S100A10, as the key endothelial receptor bringing together both plasminogen and tPA to optimise plasmin generation at the surface of the vascular wall [27].…”
Section: Discussionmentioning
confidence: 99%
“…Thrombin activates thrombin-activatable fibrinolysis inhibitor, which inhibits fibrinolysis. 21 In patients with RA and ankylosing spondylitis, TNF-α inhibition reduced PAI-1 and decreased the PAI-1/t-PA ratio. This means that TNF-α is likely involved in inhibition of the fibrinolytic system among patients with chronic rheumatologic conditions.…”
Section: Mechanisms Linking Inflammation and Venous Thrombosismentioning
confidence: 99%
“…Inhibition of the fibrinolytic system in vivo may occur either at the level of plasmin by ␣ 2 -antiplasmin or ␣ 2 -macroglobulin. Inhibition can also be at the level of tPA/ uPA (3,4), mainly by plasminogen activator inhibitor type-1 (PAI-1), which forms a suicide complex with tPA or uPA (5).…”
mentioning
confidence: 99%